PENGARUH KEMUDAHAN, PROMOSI DAN KEPUASAN TRANSAKSI ONLINESHOPPING TERHADAP KEPUTUSAN PEMBELIAN ONLINE (Survey Pada Konsumen Shopee.co.id) - Elondri Elondri (Jurnal Apresiasi Ekonomi, 2017)
This reserch is intended to see how ease, promotion and online transaction satisfaction affect online purchasing decisions (Survey on Shopee.co.id Consumers). From the result of this study obtained the convenience variables(X1) promotion (X2) and transaction satisfaction (X3) significant effect on the decision of online purchasing (Y) where the coefficient of multiple regression is 0,728 with a significant level of 0,000. The amount of influence of ease, promotion and satisfaction of online transaction to the decision to the decision of online purchase, from t test which can be seen in coeffecient table shows that alpha value for ease variable equal to 0,535 significant, promotion equal to 0,448 significant and variable of online transaction of 0,384 significant. This study was conducted using a sample of 100 people who have used shopee at least one time transaction. Keywords: Purchase Decision, Ease, Promotion andTransaction Satisfaction